Environmental support and entrepreneurial intentions: Exploring the mediating role of attitude and behavioural control and moderating effect of family background - Kwaku Amofah; Michael Gameli Dziwornu; Tomasz Rachwał; Ramon Saladrigues; Fred Fosu Agyarko (Entrepreneurial Business and Economics Review (EBER), 2024)
Objective: The objective of the article is to investigate the relationship between environmental support and entrepreneurial intention, as well as the mediating and moderating effects involved. Research Design & Methods: A web-based survey was conducted among a sample of 612 students from institutions of higher education in Spain and Poland. Structural equation modelling (SEM) was used to evaluate the conceptual framework and hypotheses. Findings: The findings revealed a positive impact of environmental support (ENSUP) on attitude, behavioural control, and intentions. Furthermore, the research reveals that attitude and behavioural control act as mediating factors in the relationship between ENSUP and intentions. The research showed that environmental support significantly predicted attitudes and intentions among Spanish students but not Poles. Moreover, the influence of support on perceived behavioural control was greater for individuals from non-entrepreneurial backgrounds compared to those with entrepreneurial backgrounds. Lastly, the influence of a person's attitude towards entrepreneurship on their level of entrepreneurial intentions was stronger in families with entrepreneurship backgrounds compared to families without such a history. Implications & Recommendations: The practical implications of this research extend to universities and policymakers, providing recommendations for supporting young entrepreneurs and their networks. Contribution & Value Added: This article contributes to the existing entrepreneurship literature by enhancing the understanding of the connection between environmental support and intentions, the mediating role of attitude and behavioural control, and the moderating effect of family background.
Keywords: I23; L26; 330; attitude; environmental support; perceived behavioural control/entrepreneurial self-efficacy; Poland; Spain